(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This Project is an android application enabled with IOT and ASL. Which aids the people with visual and hearing impairments to learn a new language? Initially the application will prompt the user to select how he is differently abled (deaf or blind).Now based on the option selected for blind people the entire UI will be converted into voice recognition system and text to Speech ,Hence the user can orally listen and learn and to learn to write, a special interface called Braille Keyboard is used ..Three foreign languages are included in this project namely English French and German. The Alphabets along with the Braille codes will be taught to the blind people. The Main Novelty of this project is that a Braille keyboard is interfaced with the application. If the user is deaf, The UI will become touch based .Now the user will start learning visually and he will understand the words through ASL .After each lesson the user will be tested on their understanding. The entire features of the application is designed based on the requirements gathered from the blind and deaf students by interacting with them in person . So the main advantage of this application is that it will be user friendly for the actual real time end user. Every lesson can be replayed any number of times until the user understands it thoroughly phones. The application assists the blind people and make their learning process easier with voice interface and in addition a Braille keyboard is also being used .They will be given a clearer vision on the Braille code for each and every alphabet The application assists the hearing impaired people to learn a new language by the standard sign language , the ASL.